2005
DOI: 10.1016/j.apsusc.2005.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Surface laser-glazing of plasma-sprayed thermal barrier coatings

Abstract: Atmospheric plasma sprayed (APS) ZrO 2 -8%WtY 2 O 3 thermal barrier coatings (TBCs) were subjected to a CO 2 continuous wave laser-glazing process in order to generate an external dense layer produced by different processing parameters. For that purpose, different beam scanning speeds and track overlapping were chosen.Surface roughness has been reduced significantly after laser-glazing. Despite the surface crack network, all laser-glazed specimens presented a fully dense and porous free external layer with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 20 publications
0
41
0
1
Order By: Relevance
“…4a,b,c), XRD analyses revealed, for all three series of coatings a polycrystalline structure composed solely by the nontransformable t' tetragonal phase which indicates that both laser systems are suitable for surface treatment without structural modification of zirconia. Moreover, ZrO 2 -8wt%Y 2 O 3 plasma-sprayed coatings may contain small amounts of residual monoclinic phase that can be suppressed by laser-glazing [10,11,31]. It was also detected some minor relative peak intensity variation due to columnar grain orientation caused by the laser-glazing process.…”
Section: Structural Analysis and Phase Destabilizationmentioning
confidence: 85%
See 2 more Smart Citations
“…4a,b,c), XRD analyses revealed, for all three series of coatings a polycrystalline structure composed solely by the nontransformable t' tetragonal phase which indicates that both laser systems are suitable for surface treatment without structural modification of zirconia. Moreover, ZrO 2 -8wt%Y 2 O 3 plasma-sprayed coatings may contain small amounts of residual monoclinic phase that can be suppressed by laser-glazing [10,11,31]. It was also detected some minor relative peak intensity variation due to columnar grain orientation caused by the laser-glazing process.…”
Section: Structural Analysis and Phase Destabilizationmentioning
confidence: 85%
“…Moreover, this post-treatment technique is suitable for surface treatment without structural modification of the zirconia nontransformable tetragonal phase because of the rapid solidification and subsequent cooling [10,11,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These perpendicular cracks on the surface of a densified coating can increase the thermal shock resistance up to four times due to the accommodation of tensions. 24 Recent studies by Batista et al 25 have shown that the APS laser glazing of ZrO 2 -8 wt %Y 2 O 3 coatings with CO 2 systems reduces the defects and inhomogeneity of Y 2 O 3 caused by thermal spraying. The rapid cooling involved in this process also eliminates the residual monoclinic phase but leaves small traces of phase tЈ.…”
Section: A Laser Glazing Of Tbcsmentioning
confidence: 99%
“…Surface modification techniques such as plasma vapor deposition, brush plating, plasma surface metallurgy technology and chemical vapor deposition are widely used in fabricating high wear resistance, oxidation resistance and corrosion resistance coating. (Batista et al, 2005).The materials used for surface coating may show different resistances against thermal cracking as compared to reference materials and the mechanism behind the thermal fatigue failure of coating surfaces are still not fully explored. Difficulties meeting the effective coating requirement caused surface treatment are more preferable in protecting dies from premature failure (Tsai, Lee, & Chang, 2007;Xu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%